High-strength durable nanometer string for Chinese zither

By using nanoreinforced materials and multi-layer braided structures in the Guzheng strings, combined with nanocoating and heat treatment technology, the problems of easy breakage, unstable tension, poor durability and difficulty in tuning are solved, and higher strength, wear resistance and sound quality stability are achieved.

CN119516980AInactive Publication Date: 2025-02-25郑博淇
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411668051.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent
Patent Text Reader

Abstract

The invention discloses a high-strength durable nano string for a Chinese zither. The high-strength durable nano string is prepared by the following steps: S1, material selection and nano technology application; S1.1, nano material selection: selecting nano carbon fibers, nano ceramic composite materials or high-strength nano polymers as base materials; the materials have extremely high strength and toughness in microstructure, and can effectively enhance the tensile strength and durability of strings. Through the nano reinforced material, the strings have higher tensile strength and wear resistance, can bear larger tension, and are longer in service life and stable in tone quality: the tension and elasticity of the strings are accurately regulated and controlled, so that intonation stability and clear and pure tone quality can be kept in long-time use; the application of the nano coating and the composite material enables the string to have better moisture resistance and oxidation resistance, reduces the influence of environmental factors on the tone quality, and through the design of the high-strength durable Chinese zither string based on the nano technology, the performance of the string can be significantly improved, the service life of the string can be prolonged, and the stability of the tone quality can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of guzheng strings, in particular to a high-strength and durable nanometer string for guzheng. Background Art

[0002] The strings of a guzheng are usually composed of six or more strings, each with different materials and tensions, resulting in different timbres. Traditionally, the strings of a guzheng were mostly made of silk or steel, but modern guzhengs often use steel or nylon strings. These strings transmit vibrations through the bridge and sound post to produce different pitches. The guzheng has a wide range of sounds, from deep bass to clear high notes, and the material and tension of the strings directly affect the timbre of the sound and the feel of playing.

[0003] In the prior art, the strength of the Guzheng strings has the following disadvantages: easy to break: traditional silk strings are easily affected by moisture and temperature changes, resulting in a decrease in strength and easy to break, especially during frequent tuning or use. Although steel strings are more durable, they may still break if over-tightened; unstable tension: strings of different materials (such as silk strings, steel strings, and nylon strings) may have uneven tension due to differences in manufacturing processes and materials, thereby affecting the stability of the sound quality. Frequent tuning or playing, changes in string tension may lead to unstable pitch; poor durability: strings of certain materials, such as silk strings, are easily affected by the external environment (such as moisture, sunlight, etc.) and lose elasticity, resulting in weakened timbre and strength, and a short service life; difficult tuning: although modern Guzheng uses more durable steel strings, the tension and pitch of the strings may need to be adjusted frequently for certain specific pitch and sound quality requirements. The hardness of steel strings is higher, and greater force is required to tune, which may increase the difficulty of tuning.

[0004] For this reason, we propose a high-strength and durable nano-string for guzheng. Summary of the invention

[0005] To achieve the above object, the present invention provides the following technical solution: a high-strength and durable nano-string for guzheng, comprising the following steps:

[0006] S1: Material selection and nanotechnology application

[0007] S1.1: Nanomaterial selection: Choose nano-carbon fiber, nano-ceramic composite material or high-strength nano-polymer as the base material. These materials have extremely high strength and toughness in microstructure, which can effectively enhance the tensile strength and durability of the strings;

[0008] S1.2: Nano-reinforced composites: Composites made by combining nanoparticles (such as carbon nanotubes, graphene, etc.) with traditional high-elastic fibers (such as nylon or polyester). These nanoparticles can significantly improve the string's tensile resistance, wear resistance, and fatigue resistance.

[0009] S2: Structural design and optimization

[0010] S2.1: String braiding structure: Considering the sound quality and durability, a multi-layer braiding structure (such as three-strand braiding, six-strand braiding) is designed, and each layer uses different nanomaterials, with wear-resistant nanomaterials for the outer layer and highly elastic nanopolymers for the inner layer. This multi-layer structure can effectively disperse the tension and enhance the stability of the string;

[0011] S2.2: String diameter and tension: Design the diameter and tension of the strings according to the sound quality requirements of the guzheng. A nano-microstructure control layer can be introduced inside the string to achieve a more precise pitch adjustment capability.

[0012] S3: Manufacturing Process

[0013] S3.1: Nanomaterial preparation: The selected nanomaterials are synthesized and dispersed to ensure uniform distribution. Carbon nanotubes and graphene particles can be combined with highly elastic fibers by solution method or melt mixing method to form nanocomposite fibers;

[0014] S3.2: Stretching and heat treatment: The nanocomposite material is stretched at high temperature to improve its strength and elastic modulus. At the same time, the microstructure is optimized through heat treatment to enhance the ductility and toughness of the strings. This can increase the service life of the strings and make them more stable.

[0015] S4 Surface Treatment

[0016] S4.1: Nano coating technology: Use nano coating technology to coat a thin film on the surface of the string to enhance its wear resistance and corrosion resistance. The nano coating can be a nano ceramic coating or a super hydrophobic coating, which can reduce the contact of the string with moisture in the air and prevent corrosion or deformation;

[0017] S4.2: Surface smoothing: To ensure the sound quality and touch of the strings, the surface needs to be finely polished to remove tiny defects. Through nano-polishing technology, the smoothness of the string surface is optimized, thereby improving the feel and purity of the tone when playing.

[0018] S5: Testing and Tuning

[0019] S5.1: Tensile and fatigue testing: The manufactured nano strings are subjected to multiple rounds of tensile, fatigue, and fracture tests to ensure their stability at room temperature, humidity, and temperature changes. These tests can verify the durability and elasticity of the strings to ensure that they can maintain good performance in long-term use;

[0020] S5.2: Sound quality evaluation: Tone test is performed to evaluate the sound quality of the nano strings. The test contents include pitch stability, fullness, clarity and persistence of the tone. The audio response of the strings can be measured by a spectrum analyzer to ensure that its sound quality meets the requirements of the Guzheng.

[0021] S6: Mass production and optimization

[0022] S6.1: Optimization of large-scale production process: After small-scale trial production, optimize and adjust the process to ensure the stability of production efficiency and product quality. For example, use a more precise temperature control system to control the string stretching process and optimize the nano-coating coating process to ensure that large-scale production products have consistent quality;

[0023] S6.2: Cost control and market promotion: Under the premise of ensuring quality, design a reasonable production process to reduce manufacturing costs. Through market research, understand consumers' demand for new nano strings, carry out appropriate publicity and promotion, and gradually launch them into the market.

[0024] Preferably, the material in step S1 includes carbon nanotubes: carbon nanotubes have very high strength and excellent electrical conductivity, low density and strong rigidity, and are suitable as reinforcing materials. By chemically modifying the surface of carbon nanotubes, they can be better combined with polymer fibers to form high-strength composite materials. Graphene: graphene has extremely strong mechanical properties and chemical stability, and can improve the strength and fatigue resistance of materials at the nanometer level. In guzheng strings, graphene can improve fracture strength and compression resistance. High-performance polymers (such as polyester, nylon): these polymers have good elasticity and toughness. Selecting high-quality polymer fibers and compounding them with nanomaterials can greatly improve the overall performance of the strings.

[0025] Preferably, the material preparation in step S1 includes preparing carbon nanotubes by chemical vapor deposition (CVD), uniformly dispersing nanoparticles (carbon nanotubes, graphene, etc.) into a polymer solution by a solution mixing method, and then drawing them into fibers by a spinning process.

[0026] Preferably, in step S2, the braided structure is designed as follows: different braided structures are used to enhance the durability and elasticity of the strings. By weaving three, six, or even nine strands, the fiber directions inside each string are different, which can better share the tension. The outer layer uses wear-resistant nano-coated fibers, and the inner layer uses highly elastic nano-reinforced polymers to enhance the fatigue resistance of the strings. The diameter and tension of the strings are designed as follows: according to the sound quality requirements of the guzheng, a suitable string diameter is designed. Usually, the diameter of the bass strings is thicker and the treble strings are thinner. During the design, the optimal structure of the strings is determined by calculating their length, tension, and elastic modulus to ensure that the tension of the strings is stable. In this process, the performance of the strings under different structures and tensions can be simulated by finite element analysis (FEA), and the design can be optimized to ensure the stability and ductility of the sound quality.

[0027] Preferably, in step S3, nanomaterial synthesis and dispersion: when nanomaterials such as carbon nanotubes or graphene are mixed with polymer substrates, surface modification treatment is first required. Common methods include oxidation treatment, chemical grafting, etc., which are used to improve the surface affinity of nanomaterials and improve their adhesion to substrates. Then, ultrasonic dispersion technology is used to evenly disperse nanoparticles in polymer solution to avoid agglomeration and ensure uniform distribution of nanomaterials in fibers. Spinning process: the prepared nanocomposite material is drawn into fibers by spinning technology. Common methods include solution spinning and melt spinning. During the spinning process, factors such as temperature, humidity, and stretching rate are adjusted to control the diameter and tensile strength of the fiber. An electron microscope (SEM) is used to observe the distribution of nanomaterials and the microstructure of the fiber to ensure the bonding effect of nanoparticles with the substrate. Stretching and heat treatment: During the manufacturing process, the spun nanofibers are stretched to improve their mechanical properties. By controlling the stretch ratio and heat treatment temperature, the crystal structure and molecular arrangement of the fiber are optimized to further improve its strength and toughness. The heat treatment process can also be used to remove internal stress in the material, reduce fiber fatigue loss, and extend the service life of the strings.

[0028] Preferably, in step S4, the nano coating technology: a nano ceramic coating is applied to the surface of the strings using chemical vapor deposition (CVD) or solution impregnation. The ceramic coating has high hardness, wear resistance and corrosion resistance, and can effectively improve the durability of the surface of the strings. Another option is to use a super hydrophobic coating to make the surface of the strings difficult for water droplets to adhere to, thereby preventing moisture from affecting the strings. Surface smoothing: nano polishing technology is used on the surface of the strings to optimize their surface smoothness. This can be achieved through ultra-precision machining or nanoparticle polishing agents to ensure that the surface of the strings is smooth and flawless, and to avoid friction that affects the playing feel.

[0029] Preferably, in step S5, the stretching and fatigue test: a tensile tester is used to perform a stretching test on the strings, and the stress-strain curves of the strings under different tensile strengths are recorded. Through these tests, the maximum bearing strength and elastic modulus of the strings can be evaluated. A fatigue testing machine is used to perform repeated tensile tests to observe the fatigue life of the strings to ensure that they will not break or deform during long-term use. Sound quality evaluation: a spectrum analyzer is used to detect the sound quality of the strings. The test content includes: pitch stability: the tuning accuracy of the strings is ensured through pitch testing, and sound quality evaluation: the audio signal is analyzed using sound analysis software to evaluate the fullness and clarity of the timbre of the strings. Ensure that the strings can maintain stable sound quality during long-term use.

[0030] Preferably, in step S6, large-scale production process optimization is performed: after small-batch production, the process is continuously optimized through production data feedback to ensure that the quality of the strings can be guaranteed at every stage of the production process. By introducing an automated production line, production efficiency is improved and human errors are reduced. Further optimization of coating technology, stretching process and heat treatment process is performed to improve production efficiency and reduce costs, cost control and market promotion: through the improvement of production processes, unit production costs are reduced. At the same time, through market research and feedback, understand consumers' needs and expectations for new nano strings, formulate reasonable pricing strategies, and ensure that new products can quickly enter the market and gain consumer recognition.

[0031] Compared with the prior art, the present invention provides a high-strength and durable nano-string for guzheng, which has the following beneficial effects:

[0032] The high-strength and durable nano strings have high tensile strength and wear resistance through nano-reinforced materials, can withstand greater tension, have a long service life, and stable sound quality: the tension and elasticity of the strings are precisely controlled to maintain stable pitch during long-term use, and the sound quality is clear and pure. The application of nano-coating and composite materials makes the strings better resistant to moisture and oxidation, reducing the impact of environmental factors on the sound quality. Through this high-strength and durable guzheng string design based on nanotechnology, the performance of the strings can be significantly improved, their service life can be increased, the stability of the sound quality can be guaranteed, and at the same time a better experience can be brought to the guzheng playing. DETAILED DESCRIPTION

[0033] The following will be combined with the scheme in the embodiment of the present invention to clearly and completely describe the technical scheme in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Example

[0035] An embodiment of a high-strength and durable nano-string for guzheng

[0036] A high-strength and durable nano-string for guzheng, comprising the following steps:

[0037] S1: Material selection and nanotechnology application

[0038] S1.1: Nanomaterial selection: Choose nano-carbon fiber, nano-ceramic composite material or high-strength nano-polymer as the base material. These materials have extremely high strength and toughness in microstructure, which can effectively enhance the tensile strength and durability of the strings;

[0039] S1.2: Nano-reinforced composites: Composites made by combining nanoparticles (such as carbon nanotubes, graphene, etc.) with traditional high-elastic fibers (such as nylon or polyester). These nanoparticles can significantly improve the string's tensile resistance, wear resistance, and fatigue resistance.

[0040] S2: Structural design and optimization

[0041] S2.1: String braiding structure: Considering the sound quality and durability, a multi-layer braiding structure (such as three-strand braiding, six-strand braiding) is designed, and each layer uses different nanomaterials, with wear-resistant nanomaterials for the outer layer and highly elastic nanopolymers for the inner layer. This multi-layer structure can effectively disperse the tension and enhance the stability of the string;

[0042] S2.2: String diameter and tension: Design the diameter and tension of the strings according to the sound quality requirements of the guzheng. A nano-microstructure control layer can be introduced inside the string to achieve a more precise pitch adjustment capability.

[0043] S3: Manufacturing Process

[0044] S3.1: Nanomaterial preparation: The selected nanomaterials are synthesized and dispersed to ensure uniform distribution. Carbon nanotubes and graphene particles can be combined with highly elastic fibers by solution method or melt mixing method to form nanocomposite fibers;

[0045] S3.2: Stretching and heat treatment: The nanocomposite material is stretched at high temperature to improve its strength and elastic modulus. At the same time, the microstructure is optimized through heat treatment to enhance the ductility and toughness of the strings. This can increase the service life of the strings and make them more stable.

[0046] S4 Surface Treatment

[0047] S4.1: Nano coating technology: Use nano coating technology to coat a thin film on the surface of the string to enhance its wear resistance and corrosion resistance. The nano coating can be a nano ceramic coating or a super hydrophobic coating, which can reduce the contact of the string with moisture in the air and prevent corrosion or deformation;

[0048] S4.2: Surface smoothing: To ensure the sound quality and touch of the strings, the surface needs to be finely polished to remove tiny defects. Through nano-polishing technology, the smoothness of the string surface is optimized, thereby improving the feel and purity of the tone when playing.

[0049] S5: Testing and Tuning

[0050] S5.1: Tensile and fatigue testing: The manufactured nano strings are subjected to multiple rounds of tensile, fatigue, and fracture tests to ensure their stability at room temperature, humidity, and temperature changes. These tests can verify the durability and elasticity of the strings to ensure that they can maintain good performance in long-term use;

[0051] S5.2: Sound quality evaluation: Tone test is performed to evaluate the sound quality of the nano strings. The test contents include pitch stability, fullness, clarity and persistence of the tone. The audio response of the strings can be measured by a spectrum analyzer to ensure that its sound quality meets the requirements of the Guzheng.

[0052] S6: Mass production and optimization

[0053] S6.1: Optimization of large-scale production process: After small-scale trial production, optimize and adjust the process to ensure the stability of production efficiency and product quality. For example, use a more precise temperature control system to control the string stretching process and optimize the nano-coating coating process to ensure that large-scale production products have consistent quality;

[0054] S6.2: Cost control and market promotion: Under the premise of ensuring quality, design a reasonable production process to reduce manufacturing costs. Through market research, understand consumers' demand for new nano strings, carry out appropriate publicity and promotion, and gradually launch them into the market.

[0055] Specifically, the materials in step S1 include carbon nanotubes: carbon nanotubes have very high strength and excellent electrical conductivity, low density and strong rigidity, and are suitable as reinforcing materials. By chemically modifying the surface of carbon nanotubes, they can be better combined with polymer fibers to form high-strength composite materials. Graphene: Graphene has extremely strong mechanical properties and chemical stability, and can improve the strength and fatigue resistance of materials at the nanometer level. In Guzheng strings, graphene can improve fracture strength and compressive resistance. High-performance polymers (such as polyester and nylon): These polymers have good elasticity and toughness. Selecting high-quality polymer fibers and compounding them with nanomaterials can greatly improve the overall performance of the strings.

[0056] Specifically, the material preparation in step S1 includes preparing carbon nanotubes by chemical vapor deposition (CVD), uniformly dispersing nanoparticles (carbon nanotubes, graphene, etc.) into a polymer solution by a solution mixing method, and then drawing them into fibers by a spinning process.

[0057] Specifically, in step S2, the braiding structure design: different braiding structures are used to enhance the durability and elasticity of the strings. By weaving three, six, or even nine strands, the fiber directions inside each string are different, which can better share the tension. The outer layer uses wear-resistant nano-coated fibers, and the inner layer uses highly elastic nano-reinforced polymers to enhance the fatigue resistance of the strings. The diameter and tension of the strings are designed: according to the sound quality requirements of the guzheng, a suitable string diameter is designed. Usually, the diameter of the bass strings is thicker and the treble strings are thinner. During the design, the optimal structure of the string is determined by calculating its length, tension, and elastic modulus to ensure that the tension of the string is stable. In this process, the performance of the strings under different structures and tensions can be simulated by finite element analysis (FEA), and its design can be optimized to ensure the stability and ductility of the sound quality.

[0058] Specifically, in step S3, nanomaterial synthesis and dispersion: when nanomaterials such as carbon nanotubes or graphene are mixed with a polymer substrate, surface modification treatment is first required. Common methods include oxidation treatment, chemical grafting, etc., which are used to improve the surface affinity of nanomaterials and improve their adhesion to the substrate. Then, ultrasonic dispersion technology is used to evenly disperse nanoparticles in the polymer solution to avoid agglomeration and ensure uniform distribution of nanomaterials in the fiber. Spinning process: The prepared nanocomposite material is drawn into fibers by spinning technology. Common methods include solution spinning and melt spinning. During the spinning process, factors such as temperature, humidity, and stretching rate are adjusted to control the diameter and tensile strength of the fiber. An electron microscope (SEM) is used to observe the distribution of nanomaterials and the microstructure of the fiber to ensure the bonding effect of nanoparticles with the substrate. Stretching and heat treatment: During the manufacturing process, the spun nanofibers are stretched to improve their mechanical properties. By controlling the stretch ratio and heat treatment temperature, the crystal structure and molecular arrangement of the fiber are optimized to further improve its strength and toughness. The heat treatment process can also be used to remove internal stress in the material, reduce fiber fatigue loss, and extend the service life of the strings.

[0059] Specifically, in step S4, the nano-coating technology: a nano-ceramic coating is applied to the surface of the strings using chemical vapor deposition (CVD) or solution impregnation. The ceramic coating has high hardness, wear resistance and corrosion resistance, and can effectively improve the durability of the surface of the strings. Another option is to use a super-hydrophobic coating to make the surface of the strings difficult for water droplets to adhere to, thereby preventing moisture from affecting the strings. Surface smoothing: Nano-polishing technology is used on the surface of the strings to optimize their surface smoothness. This can be achieved through ultra-precision machining or nano-particle polishing agents to ensure that the surface of the strings is smooth and flawless, and to avoid friction that affects the playing feel.

[0060] Specifically, in step S5, the tensile and fatigue test: use a tensile testing machine to perform a tensile test on the strings, and record the stress-strain curves of the strings at different tensile strengths. Through these tests, the maximum bearing strength and elastic modulus of the strings can be evaluated. Use a fatigue testing machine to perform repeated tensile tests to observe the fatigue life of the strings to ensure that they will not break or deform during long-term use. Sound quality evaluation: use a spectrum analyzer to detect the sound quality of the strings. The test content includes: pitch stability: ensure the tuning accuracy of the strings through pitch testing, sound quality evaluation: use sound analysis software to analyze audio signals and evaluate the fullness, clarity and other indicators of the string's tone. Ensure that the strings can maintain stable sound quality during long-term use.

[0061] Specifically, in step S6, large-scale production process optimization: after small-batch production, the process is continuously optimized through production data feedback to ensure that the quality of the strings can be guaranteed at every stage of the production process. By introducing an automated production line, production efficiency is improved and human errors are reduced. Further optimization of coating technology, stretching process and heat treatment process to improve production efficiency and reduce costs, cost control and market promotion: through the improvement of production processes, the unit production cost is reduced. At the same time, through market research and feedback, understand the needs and expectations of consumers for new nano strings, formulate a reasonable pricing strategy, and ensure that new products can quickly enter the market and gain consumer recognition.

[0062] Through the above technical scheme, in the present invention, firstly, nano-reinforced materials (such as carbon nanotubes, graphene, etc.) are used to make the strings have extremely high strength and fatigue resistance, and can withstand greater tension and longer use without breaking easily; secondly, nano-coating technology improves the wear resistance and corrosion resistance of the strings, reduces the impact of the external environment on the strings, and prolongs the service life; at the same time, the optimized braiding structure and elastic design ensure that the sound quality of the strings is stable and the tone is clear and pure; in addition, the fine surface treatment and smoothness design enhance the feel and tone performance during playing, providing a better playing experience. Although the embodiments of the present invention have been shown and described, it can be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the attached claims and their equivalents.

Claims

1. A high-strength and durable nano-string for guzheng, characterized by: The following steps are involved: S1: Material selection and nanotechnology application S1.1: Nanomaterial selection: Choose nano-carbon fiber, nano-ceramic composite material or high-strength nano-polymer as the base material. These materials have extremely high strength and toughness in microstructure, which can effectively enhance the tensile strength and durability of the strings; S1.2: Nano-reinforced composites: Composites made by combining nanoparticles (such as carbon nanotubes, graphene, etc.) with traditional high-elastic fibers (such as nylon or polyester). These nanoparticles can significantly improve the string's tensile resistance, wear resistance, and fatigue resistance. S2: Structural design and optimization S2.1: String braiding structure: Considering the sound quality and durability, a multi-layer braiding structure (such as three-strand braiding, six-strand braiding) is designed. Each layer uses different nanomaterials, the outer layer uses wear-resistant nanomaterials, and the inner layer uses highly elastic nanopolymers. This multi-layer structure can effectively disperse the tension and enhance the stability of the string; S2.2: String diameter and tension: Design the diameter and tension of the strings according to the sound quality requirements of the guzheng. A nano-microstructure control layer can be introduced inside the string to achieve a more precise pitch adjustment capability. S3: Manufacturing Process S3.1: Nanomaterial preparation: The selected nanomaterials are synthesized and dispersed to ensure uniform distribution. Carbon nanotubes and graphene particles can be combined with highly elastic fibers by solution method or melt mixing method to form nanocomposite fibers; S3.2: Stretching and heat treatment: The nanocomposite material is stretched at high temperature to improve its strength and elastic modulus. At the same time, the microstructure is optimized through heat treatment to enhance the ductility and toughness of the strings. This can increase the service life of the strings and make them more stable. S4 Surface Treatment S4.1: Nano coating technology: Use nano coating technology to coat a thin film on the surface of the string to enhance its wear resistance and corrosion resistance. The nano coating can be a nano ceramic coating or a super hydrophobic coating, which can reduce the contact of the string with moisture in the air and prevent corrosion or deformation; S4.2: Surface smoothing: To ensure the sound quality and touch of the strings, the surface needs to be finely polished to remove tiny defects. Through nano-polishing technology, the smoothness of the string surface is optimized, thereby improving the feel and purity of the tone when playing. S5: Testing and Tuning S5.1: Tensile and fatigue testing: The manufactured nano strings are subjected to multiple rounds of tensile, fatigue, and fracture tests to ensure their stability at room temperature, humidity, and temperature changes. These tests can verify the durability and elasticity of the strings to ensure that they can maintain good performance in long-term use; S5.2: Sound quality evaluation: Tone test is performed to evaluate the sound quality of the nano strings. The test contents include pitch stability, fullness, clarity and persistence of the tone. The audio response of the strings can be measured by a spectrum analyzer to ensure that its sound quality meets the requirements of the Guzheng. S6: Mass production and optimization S6.1: Optimization of large-scale production process: After small-scale trial production, optimize and adjust the process to ensure the stability of production efficiency and product quality. For example, use a more precise temperature control system to control the string stretching process and optimize the coating process of the nano coating to ensure that the mass-produced products have consistent quality; S6.2: Cost control and market promotion: Under the premise of ensuring quality, design a reasonable production process to reduce manufacturing costs. Through market research, understand consumers' demand for new nano strings, carry out appropriate publicity and promotion, and gradually launch them into the market.

2. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: The materials in step S1 include carbon nanotubes: carbon nanotubes have very high strength and excellent electrical conductivity, low density and strong rigidity, and are suitable as reinforcing materials. By chemically modifying the surface of carbon nanotubes, they can be better combined with polymer fibers to form high-strength composite materials. Graphene: Graphene has extremely strong mechanical properties and chemical stability, and can improve the strength and fatigue resistance of materials at the nano level. In guzheng strings, graphene can improve fracture strength and compression resistance. High-performance polymers (such as polyester, nylon): These polymers have good elasticity and toughness. Selecting high-quality polymer fibers and compounding them with nanomaterials can greatly improve the overall performance of the strings.

3. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: The material preparation in step S1 includes preparing carbon nanotubes by chemical vapor deposition (CVD), uniformly dispersing nanoparticles (carbon nanotubes, graphene, etc.) into a polymer solution by a solution mixing method, and then drawing them into fibers by a spinning process.

4. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: The braiding structure design in step S2: using different braiding structures to enhance the durability and elasticity of the strings. By braiding three, six, or even nine strands, the fiber directions inside each string are different, which can better share the tension. The outer layer uses wear-resistant nano-coated fibers, and the inner layer uses highly elastic nano-reinforced polymers to enhance the fatigue resistance of the strings. The diameter and tension of the strings are designed: according to the sound quality requirements of the guzheng, the appropriate string diameter is designed. Usually, the diameter of the bass strings is thicker and the treble strings are thinner. During the design, the length, tension, and elastic modulus of the strings are calculated to determine their optimal structure to ensure the stability of the tension of the strings. In this process, the performance of the strings under different structures and tensions can be simulated by finite element analysis (FEA), and their design can be optimized to ensure the stability and ductility of the sound quality.

5. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: Nanomaterial synthesis and dispersion in step S3: When nanomaterials such as carbon nanotubes or graphene are mixed with a polymer substrate, surface modification treatment is first required. Common methods include oxidation treatment, chemical grafting, etc., which are used to improve the surface affinity of nanomaterials and improve their adhesion to the substrate. Then, ultrasonic dispersion technology is used to evenly disperse the nanoparticles in the polymer solution to avoid agglomeration and ensure the uniform distribution of nanomaterials in the fiber. Spinning process: The prepared nanocomposite material is drawn into fibers by spinning technology. Common methods include solution spinning and melt spinning. During the spinning process, factors such as temperature, humidity, and stretching rate are adjusted to control the diameter and tensile strength of the fiber. The distribution of nanomaterials and the microstructure of the fiber are observed using an electron microscope (SEM) to ensure the bonding effect of the nanoparticles with the substrate. Stretching and heat treatment: During the manufacturing process, the spun nanofibers are stretched to improve their mechanical properties. By controlling the stretching ratio and heat treatment temperature, the crystal structure and molecular arrangement of the fiber are optimized to further improve its strength and toughness. The heat treatment process can also be used to remove internal stress in the material, reduce fiber fatigue loss, and extend the service life of the strings.

6. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: Nano coating technology in step S4: Nano ceramic coating is applied to the surface of the strings by chemical vapor deposition (CVD) or solution impregnation. The ceramic coating has high hardness, wear resistance and corrosion resistance, and can effectively improve the durability of the surface of the strings. Another option is to use a super hydrophobic coating to make the surface of the strings difficult for water droplets to adhere to, thereby preventing moisture from affecting the strings. Surface smoothing: Nano polishing technology is used on the surface of the strings to optimize their surface smoothness. This can be achieved through ultra-precision machining or nanoparticle polishing agents to ensure that the surface of the strings is smooth and flawless, and to avoid friction that affects the playing feel.

7. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: In step S5, the tensile and fatigue tests are as follows: the tensile test machine is used to perform tensile tests on the strings, and the stress-strain curves of the strings at different tensile strengths are recorded. Through these tests, the maximum bearing strength and elastic modulus of the strings can be evaluated. The fatigue testing machine is used to perform repeated tensile tests to observe the fatigue life of the strings to ensure that they will not break or deform during long-term use. Sound quality evaluation: a spectrum analyzer is used to detect the sound quality of the strings. The test contents include: pitch stability: the tuning accuracy of the strings is ensured through pitch testing, sound quality evaluation: the audio signal is analyzed using sound analysis software to evaluate the fullness of the timbre, clarity and other indicators of the strings. Ensure that the strings can maintain stable sound quality during long-term use.

8. The high-strength and durable nano-string for guzheng according to claim 1, characterized in that: Optimization of large-scale production process in step S6: After small-batch production, the process is continuously optimized through production data feedback to ensure that the quality of the strings can be guaranteed at every stage of the production process. By introducing an automated production line, production efficiency is improved and human errors are reduced. Further optimization of coating technology, stretching process and heat treatment process to improve production efficiency and reduce costs, cost control and market promotion: through the improvement of production process, the unit production cost is reduced. At the same time, through market research and feedback, understand the needs and expectations of consumers for the new nano strings, formulate a reasonable pricing strategy, and ensure that new products can quickly enter the market and gain consumer recognition.